Acyl-CoA hydrolysis by the high molecular weight protein 1 subunit of yersiniabactin synthetase: Mutational evidence for a cascade of four acyl-enzyme intermediates during hydrolytic editing - Suo, Zucai (The National Academy of Sciences, 2000)
Yersiniabactin (Ybt) synthetase is a three-subunit, 17-domain [7 domains in high molecular weight protein (HMWP)2, 9 in HMWP1, and 1 in YbtE] enzyme producing the virulence-conferring siderophore yersiniabactin in Yersinia pestis. The 350-kDa HMWP1 subunit contains a polyketide synthase module (KS-AT-MT(2)-KR-ACP) and a nonribosomal peptide synthetase module (Cy(3)-MT(3)-PCP(3)-TE). The full-length HMWP1 was heterologously overexpressed in Escherichia coli and purified to near homogeneity. The purified HMWP1 showed thioesterase activity toward acyl-CoAs, such as acetyl-CoA, benzoyl-CoA, and malonyl-CoA, with saturation kinetics and relative catalytic efficiencies of 172:50:1. A chain-releasing thioesterase (TE) activity is ascribed to the C-terminal TE domain, and this was substantiated by the fact that acyl-N-acetylcysteamines were hydrolyzed by the didomain PCP(3)-TE fragment of HMWP1. However, PCP(3)-TE failed to hydrolyze any of the acyl-CoAs, suggesting the TE domain does not recognize CoA moiety, thus the acyl-CoA hydrolysis by HMWP1 must involve other domains. Ser-to-Ala mutants in each of the AT, ACP, PCP(3), and TE domains reduced hydrolysis rates of the two fastest substrates, acetyl-CoA and benzoyl-CoA, by more than two orders of magnitude. Thus, the acyl-CoA hydrolysis activity requires 4 of the 9 domains of HMWP1, and it is consistent with autoacylation of the AT domain active site serine and subsequent passage of the itinerant acyl chain from AT to ACP to PCP(3) to the TE domain, a cascade of four sequential acyl-enzyme intermediates, for hydrolytic turnover. This could represent an editing pathway for this polyketide synthase/nonribosomal peptide synthetase assembly line.